2016
DOI: 10.1111/cei.12853
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-9/IL-9R axis drives γδ T cells activation in psoriatic arthritis patients

Abstract: Cytokines such as tumour necrosis factor (TNF)-α, interleukin (IL)-12, interferon (IFN)-γ, IL-23 and, more recently, IL-9, have been implicated in the initiation/maintenance of inflammation in psoriasis and psoriatic arthritis (PsA). In the present study we aimed to characterize the role of γδ T cells in peripheral blood and synovial fluid of PsA patients and to investigate their response to in-vitro stimulation with antigen or cytokines (IL-9 and IL-23). γδ T cells isolated from peripheral blood mononuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 18 publications
(22 reference statements)
1
34
0
Order By: Relevance
“…mDCs and pDCs, both capable of producing CXCL4, are increased in PsA and rheumatoid arthritis SF [35][36][37]. Furthermore, in addition to CD4 + T cells, there are other type 17 cells enriched in the PsA SF, including the type 3 innate lymphoid cells [38], CD8 T cells [39], and γδ T cells [40]. CXCL4 contribution to the IL-17 regulation in these cells still needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…mDCs and pDCs, both capable of producing CXCL4, are increased in PsA and rheumatoid arthritis SF [35][36][37]. Furthermore, in addition to CD4 + T cells, there are other type 17 cells enriched in the PsA SF, including the type 3 innate lymphoid cells [38], CD8 T cells [39], and γδ T cells [40]. CXCL4 contribution to the IL-17 regulation in these cells still needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be elucidated whether these cells express the IL‐23R. In addition, IL‐23R + Th17 cells are detected in PsA synovial fluid and IFNy + , IL‐17 + γδ T cells are found enriched in the synovial fluid compared to peripheral blood .…”
Section: Il‐23 Producing and Responding Cells In Autoimmune Arthriticmentioning
confidence: 99%
“…In particular, in some cases, uveitis has been observed after infusion (4). Moreover, it is known that zoledronic acid might induce arrhythmias (atrial fibrillation, in particular) (5).…”
Section: Could G/d T Cells Explain Adverse Effects Of Zoledronic Acidmentioning
confidence: 99%
“…Zoledronic acid indeed leads to an accumulation of intracellular isopentenyl pyrophosphate (IPP) in target cells, which in turn activates human Vg91Vd21 T cells. However, only a few reports to date have described the induction of IL-17 in human Vg91Vd21 T cells, either by zoledronate (1), or directly by phosphoantigens such as IPP (2)(3)(4)(5) or the more potent microbial hydroxyl-3methyl-but-2-enyl pyrophosphate (HMBPP) (6,7) (Table 1). Collectively, these studies showed that in healthy human blood only a minor g/d T cell population produces IL-17 upon stimulation with HMBPP or IPP, whereas IL-17-producing g/d T cell numbers can increase upon stimulation with specific cytokine mixtures, during infection or autoimmune and autoinflammatory diseases (Table 1).…”
Section: Replymentioning
confidence: 99%
See 1 more Smart Citation